Multiphoton processes in radiation of relativistic electrons in oriented crystals; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 173, iss. 1-2 - Kolchuzhkin A. (2001, 2001)
The number of bremsstrahlung photons and the resulting energy loss for an electron passing through a crystal are random quantities. The kinetic equation for the energy loss distribution has been derived and transformed into the equations for the distributions moments. The equations for the moments have been solved in continuous slowing down approximation using full screening Bethe-Heitler formulas for incoherent bremsstrahlung cross-sections and simple phenomenological expressions for coherent bremsstrahlung and channeling radiation. The solutions were used to calculate the number of "coherent" photons per unit path length and the mean energy of a photon. They were expressed in terms of the moments of energy loss distribution which can be determined experimentally. The results are compared with the data of other authors.